Pengaruh Perilaku Konsumtif Masyarakat Kecamatan Lembah Sorik Marapi Terhadap Keputusan Transaksi Chip Game Online Ditinjau Dari Persfektif Ekonomi Islam - Marwah Auliyani; Isnaini Harahap; Muhammad Syahbudi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
Many people behave consumptively and no longer pay attention to the needs that should be needed. This study aims to determine the effect of trend, association, and income on online game chip transaction decisions from the perspective of Islamic economics. This research uses quantitative methods. Analysis of multiple linear regression test data, using SPSS software version 23. The results of the T test trend variable (Tr) obtained a tcount > ttable of (3.867 > 1.674) with a significance value of 0.000 <0.05, the association variable (Pr) obtained a value tcount < ttable of (1.153 > 1.674 the significance value is 0.254 Ëƒ 0.05, the income variable is obtained by tcount > ttable of (3.102 > 1.674) with a significance value of 0.003 <0.05. And the F test shows the results of Fcount 50.389 > Ftable 2, 78, a significant value of 0.000. This indicates that the trend variable and income variable have a significant effect on online game chip transaction decisions, while the association variable has no effect on online game chip transaction decisions.